2015
DOI: 10.1063/1.4927450
|View full text |Cite
|
Sign up to set email alerts
|

Growth of epitaxial orthorhombic YO1.5-substituted HfO2 thin film

Abstract: YO1.5-substituted HfO2 thin films with various substitution amounts were grown on (100) YSZ substrates by the pulsed laser deposition method directly from the vapor phase. The epitaxial growth of film with different YO1.5 amounts was confirmed by the X-ray diffraction method. Wide-area reciprocal lattice mapping measurements were performed to clarify the crystal symmetry of films. The formed phases changed from low-symmetry monoclinic baddeleyite to high-symmetry tetragonal/cubic fluorite phases through an ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 24 publications
4
137
1
1
Order By: Relevance
“…Besides the initially reported Si, many other dopants, including Zr, 5,26,27 Y, [28][29][30][31] Al, 32 Gd, 33 Sr, 34 and La 35 have also been reported to induce the ferroelectricity in HfO 2 -based thin films. Doping is able to stabilize the o-phase of HfO 2 with appropriate dopant concentrations, because dopants with ionic sizes different from that of Hf can significantly modify the metal-oxygen bonding and further change the relative stabilities of various HfO 2 phases.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the initially reported Si, many other dopants, including Zr, 5,26,27 Y, [28][29][30][31] Al, 32 Gd, 33 Sr, 34 and La 35 have also been reported to induce the ferroelectricity in HfO 2 -based thin films. Doping is able to stabilize the o-phase of HfO 2 with appropriate dopant concentrations, because dopants with ionic sizes different from that of Hf can significantly modify the metal-oxygen bonding and further change the relative stabilities of various HfO 2 phases.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…In this connection, anisotropic stresses are required for the phase transition from tetragonal to orthorhombic, i.e., a compressive stress within the aob plane and a tensile stress along the c-axis exerted on the t-phase. There are many factors reported hitherto to be responsible for causing the anisotropic stresses and thus stabilizing the ferroelectric o-phase during the film growth, such as doping, 4,5,[23][24][25][26][27][28][29][30][31][32][33][34][35] surface energy effect, [36][37][38] island coalescence, 39 thermal expansion mismatch, 17 capping layer effect, 4,38 and formation of oxygen vacancies. 40 The following of this section will discuss each of these factors in order.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…The ferroelectricity was confirmed by D-E hysteresis measurements, which revealed P s of 16 µC/cm 2 as shown in Figure 9. The Curie temperature (T c ) was estimated to be about 623 K [39,40]. [18,19,[35][36][37][38].…”
Section: High-k Materials Hfo 2 and Zromentioning
confidence: 99%
“…Recently, transmission electron microscopy (TEM), scanning TEM (STEM), and convergent electron beam diffraction have shown that the ferroelectric phase in HfO 2 -based materials has a polar structure28. After this study, we grew a single-crystal epitaxial HfO 2 -based films with a single polar orthorhombic phase by pulsed laser deposition (PLD)30. In the previous study, we probed the polar crystal structure by XRD and annular bright-field STEM that visualized the atomic arrangement, including light O atoms30.…”
mentioning
confidence: 99%
“…After this study, we grew a single-crystal epitaxial HfO 2 -based films with a single polar orthorhombic phase by pulsed laser deposition (PLD)30. In the previous study, we probed the polar crystal structure by XRD and annular bright-field STEM that visualized the atomic arrangement, including light O atoms30.…”
mentioning
confidence: 99%